Termékek és technológiák minősítése az élelmiszeripari innovációs folyamatban - Balogh, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The fact that the food is qualified as w ith a special price determines several o f the factors o f the food industry innovational process. The developer initiating the innovation or an en trepreneur have to can, that in case o f a product developm ent how (onto w hat kind o f consum er need) w ishes to calibrate the product to be developed, how new needs o pened and that which ones the need bars. The food industry product range since peculiarly wide: the so-called ‘lifestyle’ or ‘n o v e l’ extend to foods from the traditional foods. A technology d evelopm ent task w ith a different measure jo in s product innovations representing the different novelty value furtherm ore. The study - the author m ore based on his decennial experiences - presents the peculiarities o f the food industry innovations, the econom ic co ntent o f the process, and the criteria o f his success and the measurem ent o f the success. His aim is orienting the food industry SM Os for his innovational endeavors and the layman - not food industry - inform ing a vocational audience.